Validation of Training and Acquisition of Surgical Skills in Veterinary Laparoscopic Surgery: A Review - Oviedo-Peñata, Carlos A.; Tapia-Araya, Angelo E.; Lemos, Juan D.; Riaño-Benavides, Carlos; Case, J. Brad; Maldonado-Estrada, Juan G. (Frontiers in Veterinary Science, 2020)
At present, veterinary laparoscopic surgery training is lacking in experiences that provide a controlled and safe environment where surgeons can practice specific techniques while receiving experts' feedback. Surgical skills acquired using simulators must be certified and transferable to the operating room. Most models for practicing laparoscopic skills in veterinary minimally invasive surgery are general task trainers and consist of boxes (simulators) designed for training human surgery. These simulators exhibit several limitations, including anatomic species and procedural differences, as well as general psychomotor training rather than in vivo skill recreation. In this paper, we review the existing methods of training, evaluation, and validation of technical skills in veterinary laparoscopic surgery. Content includes global and specific scales, and the conditions a structured curriculum should meet for improving the performance of novice surgeons during and after training. A focus on trainee-specific assessment and tailored-technical instruction should influence training programs. We provide a comprehensive analysis of current theories and concepts related to the evaluation and validation of simulators for training laparoscopic surgery in small animal surgery. We also highlight the need to develop new training models and complementary evaluation scales for the validation of training and acquisition of basic and advanced skills in veterinary laparoscopic surgery.